1998
DOI: 10.1074/jbc.273.1.248
|View full text |Cite
|
Sign up to set email alerts
|

Heparinase I from Flavobacterium heparinum

Abstract: Heparinases are bacterial enzymes that are powerful tools to study the physiological roles of heparin-like complex polysaccharides. In addition, heparinases have significant therapeutic applications. We had proposed earlier that cysteine 135 and histidine 203 together form the catalytic domain in heparinase I. We had also identified a heparin binding domain in heparinase I containing two positively charged clusters HB-1 and HB-2 in a primary heparin binding site and other positively charged residues in the vic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…The pattern for this enzyme is predominantly exolytic, processive (23), and not endolytic as suggested previously (27). It might be possible to generate an exclusively exolytic or a nonprocessive heparinase I by protein engineering (28). Such an enzyme would be suited more ideally for sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern for this enzyme is predominantly exolytic, processive (23), and not endolytic as suggested previously (27). It might be possible to generate an exclusively exolytic or a nonprocessive heparinase I by protein engineering (28). Such an enzyme would be suited more ideally for sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant heparin lyase I (EC 4.2.2.7), II (no EC number), and III (E.C. 4.2.2.8) were prepared as described previously (23). ⌬ 4,5 -Glycuronidase was isolated from Flavobacterium heparinum (24).…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that Cys 135 , His 203 , and Lys 199 are important in the catalytic mechanism of heparinase I (9,11,12). Through extensive site-directed mutagenesis studies, we identified other positively charged residues (Lys 132 and Lys…”
mentioning
confidence: 99%
“…) that provide the necessary microenvironment for heparinase I catalysis (12). Recent studies of heparin degradation by heparinase I revealed a processive catalytic mechanism in which heparin is predominantly degraded exolytically from the nonreducing end (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation